رۆژنامەوانیی مۆبایل و بەرهەمێنانی كۆمەڵگای تۆڕیی لای میدیاكارانی هەرێمی كوردستان (توێژینەوەیەكی مەیدانی) - محەمەد, پ.ی. د شێركۆ جەبار; عەبدولرەحمان, م.ی. ئیسماعیل عوسمان (Sulaimani Journal for Humanities, 2023)
Mobile journalism, which involves journalists producing and transmitting news through smartphones, has a significant impact on the speed and dissemination of information. Consequently, many institutions have embraced this new technology for media production and transmission. This research aims to assess the extent of smartphone usage among journalists in the Kurdistan Region, who rely on internet-based networks to exchange information among themselves and media organizations. The study methodology involves quantitative analysis using survey forms administered to journalists from 10 media institutions in the Kurdistan Region, including television, social media, web TV, and radio. The research is grounded in Manuel Castells' theory of the Network Society, which recognizes the crucial role of information technology, such as computers, the internet, and smartphones, in shaping this new era. The study's findings reveal that journalists heavily rely on smartphone technology for information production, transmission, and delivery, particularly in live coverage and breaking news situations, thereby enhancing the efficiency and speed of media message dissemination.
Keywords: network society; Mobile journalism; citizen journalism; media production; journalists